Spanish and Global Languages and Culture Program Review Dean's Review: Vandana Kohli (2021)
This is the Dean's response to the Spanish and Global Languages and Culture (SGLC) program review conducted during 2018-2019. The program was reviewed by Maria M. Carreira; Edward W. Hood; and Jeffrey Reeder. Their external reviewers report was submitted in January 2021. Any issues that emerged during the program review requiring University level attention are not included in this summary of observations and recommendations. The Dean's office will work with the appropriate academic support units to address university level issues noted by the external reviewers as part of the MOU development and implementation process.